Cytotoxic and DNA-Damaging Effects of Aronia melanocarpa, Cornus mas, and Chaenomeles superba Leaf Extracts on the Human Colon Adenocarcinoma Cell Line Caco-2 - Magdalena Efenberger-Szmechtyk; Adriana Nowak; Agnieszka Nowak (MDPI AG, 2020)
Aronia melanocarpa, Cornus mas, and Chaenomeles superba leaf extracts contain large amounts of bioactive compounds-mainly polyphenols, which possess many health benefits including anti-cancer properties. Here, we investigate the biological effects of A. melanocarpa, C. mas, and C. superba leaf extracts on the human colon adenocarcinoma cell line Caco-2. The antiproliferative activity of the extracts was measured using the MTT assay. The most cytotoxic extract was C. mas (IC50 = 0.60%). The extracts caused morphological changes in the Caco-2 cells, including partial detachment of cells, necrotic cells, chromatin condensation, cytoplasmic vacuolization, cell nuclei lysis, and nucleus fragmentation. The DNA damage in the Caco-2 cells after exposure to the leaf extracts was measured using the alkaline comet assay. The extracts increased DNA damage in a concentration dependent manner. However, at lower non-cyto- and non-genotoxic (IC0) concentrations the extracts induced DNA repair in Caco-2 cells after exposure to hydrogen peroxide. In conclusion, the results of these studies suggest that A. melanocarpa, C. mas and C. superba leaf extracts can show anticancer activity. However, further research is required on the mechanisms of anti-cancer activity by these extracts, with the application of more advanced and wide-ranging techniques including in vivo experiments.